Reviews (New blackfriars, 1995)
FRIAR IN THE WILDERNESS: EDWARD DOMINIC FENWICK OP by Loretta Petit O.P. RIGHT PRACTICAL REASON: ARISTOTLE, ACTION, AND PRUDENCE IN AQUINAS by Daniel Westberg HEIDEGGER AND CHRISTIANITY: THE HENSLEY HENSON LECTURES 1993–94 by John Macquarrie